Cover Image, Volume 9, Issue 2. (22nd February 2018) - Ng, Adolf K.Y.; Andrews, Jonathan; Babb, David; Lin, Yufeng; Becker, Austin
Abstract : The cover image, by Adolf K.Y. Ng et al., is based on the Advanced Review Implications of climate change for shipping: Opening the Arctic seas, DOI: 10.1002/wcc.507 . Photo Credit: Koi Yu Adolf Ng. Abstract : The cover image, by Adolf K.Y. Ng et al., is based on the Advanced Review Implications of climate change for shipping: Opening the Arctic seas, DOI: 10.1002/wcc.507 . Photo Credit: Koi Yu Adolf Ng.